Efeito da minociclina sobre a microglia do Locus coeruleus em um modelo esporádico para Doença de Alzheimer - Paneghini, Julia de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Alzheimer's disease (AD) is the most common neurodegenerative dementia in the world. Inflammation of the central nervous system in AD is the result of the activation of micróglia cells in response to the formation of amyloid plaques and / or hyperphosphorylation of the tau protein (NFTs), which can promote a chronic state of neuroinflammation that worsens and accelerates the progression of disease. In our previous study, we demonstrated the increased expression of beta amyloid peptide in the Locus Coeruleus (LC) in a sporadic AD model induced by intracerebroventricular injection of 2 mg / kg of streptozotocin (STZ). LC is a region that can trigger the initial neuroinflammatory process in AD. Thus, we investigated whether treatment with minocycline (micróglia inhibitor) would affect micróglia cells in the LC in rats treated with STZ. Control or STZ Wistar rats were treated for 5 consecutive days with minocycline (30 mg/kg, ip) or vehicle. After 5 days of treatment, the animals were submitted to the Barnes Maze behavioral test and immunohistochemistry was performed for LC micróglia by labeling with Iba-1. Regarding the Barnes test, we did not observe a significant difference in the number of hits in the target hole between animals in the Vehicle group, treated with Placebo or Minocycline (Vehicle-Control: 6.6 ± 2.9 vs Vehicle-Minocycline: 6.4 ± 3.1; P > 0.05). The STZ animals had a lower number of hits in the target hole than their respective vehicles (p< 0.05). We observed that the STZ-Minocycline group had a higher number of hits in the target hole than the STZ-Control group (STZ-Mino: 3.8 ± 2.9 vs STZ-Placebo: 2.2 ± 1.1; p< 0.05). We observed that the treatment with minocycline decreased the micróglia cell density in the AD model (p<0.05) and the treatment did not alter the proximity of the micróglia cells in the STZ model (p> 0.05). Likewise, after treatment with minocycline, the arborization of cells in the STZ-AD group increased (p <0.05) and the cell body decreased (p <0.05), indicating the return of the micróglia to its reactive form. We also observed a decrease in the morphological index (p<0.05), which reflects the inactivation of micróglia cells in the AD model. Our data suggest that minocycline reduced cognitive impairment, which is possibly associated with inhibition of LC micróglia.

A doença de Alzheimer (DA) é a demência neurodegenerativa mais comum no mundo. A inflamação do sistema nervoso central na DA é o resultado da ativação das células da micróglia em resposta à formação de placas amilóides e / ou hiperfosforilação da proteína tau (NTFs), que pode promover um estado crônico de neuroinflamação que piora e acelera a progressão da doença. Em estudo anterior do nosso laboratório, demonstramos o aumento da expressão do peptídeo beta amiloide no Locus Coeruleus (LC) em um modelo de DA esporádico induzido por injeção intracerebroventricular de 2 mg / kg de estreptozotocina (STZ). O LC é uma região que pode desencadear o processo neuroinflamatório inicial na DA. Assim, no presente estudo, investigamos se o tratamento com minociclina (inibidor da micróglia) afeta as células da micróglia no LC em ratos tratados com STZ. Os ratos Wistar do grupo Placebo ou STZ foram tratados por 5 dias consecutivos com minociclina (30 mg/kg, ip) ou veículo (salina + água). Após os 5 dias de tratamento, os animais foram submetidos ao teste comportamental de Barnes Maze e foi realizada a imuno-histoquímica para micróglia do LC por meio da marcação com Iba-1. Em relação ao teste de Barnes, não observamos diferença significativa no número de acertos no furo alvo entre os animais do grupo Veículo, tratados com Placebo ou Minociclina (Veículo-Placebo: 6,6 ± 2,9 vs Veículo-Minociclina: 6,4 ± 3,1; p> 0,05). Os animais STZ apresentaram menos acertos no furo alvo que seus respectivos veículos (p< 0,05). Observamos que o grupo STZ-Minociclina apresentou um número maior de acertos no furo alvo que o grupo STZ-Placebo (STZ-Mino: 3,8 ± 2,9 vs STZ-Placebo: 2,2 ± 1,1; p< 0,05). Em relação à morfologia da micróglia, o tratamento com minociclina diminuiu a densidade celular da micróglia no modelo AD (p< 0,05) e o tratamento não alterou a proximidade das células da micróglia no modelo STZ (p>0,05). Da mesma forma, após o tratamento com minociclina, a arborização das células do grupo STZ-AD aumentou (p< 0,05) e o corpo celular diminuiu (p< 0,05), indicando o retorno da micróglia à sua forma reativa. Observamos também uma diminuição do índice morfológico (p< 0,05), que reflete a inativação das células da micróglia no modelo de DA. Nossos dados sugerem que a minociclina reduziu o comprometimento cognitivo, que possivelmente está associado à inibição da micróglia LC.
Effect of minocycline on the microglia of the Locus coeruleus in a sporadic model for the treatment of Alzheimer's disease
Keywords: Neurofisiologia; Microglia; Alzheimer, Doença de; Sistema nervoso Degeneração